SIKAP ANAK PRA SEKOLAH DALAM PEMELIHARAAN KESEHATAN GIGI SETELAH EDUKASI BONEKA TANGAN DI KAWASAN RAWAN BENCANA - Mujito Mujito; Aina’ul Mardliyyatun Nisa; Sri Winarni (Poltekkes Kemenkes Malang, 2019)
Maintenance of dental health in children is important, especially by using a preventive approach, one of the efforts that can be done is education using media hand puppet education. The purpose of this research was to identifity preschool children attitudes to maintaining dental health after education using hand puppets in disaster prone areas. The types of research is description. Subject of this reasearch are 20 students on Argasiwi kinderkarten. The technique to collecting data was using questioner. Sample of respondent were taken by purposive sampling. The result of research showing if when pre test 90 percent or 18 students have positive attitudes on dental care and 10 percent or 2 students have negative attitudes on dental care. After education using hand puppets, the result of pos test 100percent or 20 students have positive attitudes on dental care. It is suggested the teacher and parent can active to give education about dental health to their child.